PENGARUH PERCEIVED PRICE, KUALITAS PRODUK, DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN RICEBOWL BABIBONG - Susilo, Giolandro Eric; Setiobudi, Auditia (Universitas Ciputra Surabaya, 2023)
The research is done to find out the effect of perceived price, product quality, and perceived value on purchase decision of ricebowl Babibong. This research is based on by research to find out what affects consumers in buying Babibong ricebowl product, that leads to perceived price, product quality and perceived value variables. The purpose of this research is to find out what indicator that affects purchase decision of Babibong customers. The method that is used for data collection in this research is purposive sampling, that is, the population that is filtered with certain criteria, and its population is gathered from Babibong Instagram social media. The sample that is used for this research is 154 people who are distributed through online media by using online questionnaires and have fulfilled the criteria that is required. Data process method uses validity test, reliability test, normality test, heteroscedaticity test, multicollinearity test, F test, t test, correlation coefficient test (R), determination coefficient test (R2). The result of this research concludes that perceived price, product quality, and perceived value affect significant on purchase decision. From the test result of those three variables can be considered vital for customers’s purchase decision, because it is commonly used and happened daily.